Rheological characteristics of dry cured ham of four Italian autochthonous genetic types of pig - Barone C.M.A.; Castellano N.; Colatruglio P.; Zullo A.; Matassino D. (5. International Symposium on the Mediterranean Pig, 2007)
The aim of this research was to evaluate rheological characteristics of dry cured ham of some Italian autochthonous genetic types (AGT) of pig. In 108 dry cured hams obtained from Calabrese (CL=29), Casertana (CT=6), Cinta senese (CS=19) and Nero Siciliano (SC=54) AGTs, rheological traits were determined on Biceps femoris (BF), Semimembranosus (Sm) and Semitendinosus (St) muscles using a Texturometer. Curing process was performed in Parma (64 hams) and in Morcone (Benevento) (44 hams) curing plants. Data were analysed using aging time as covariate and AGT, sex, curing plant, muscle and first order interaction as fixed factors. The results showed that AGT Casertana had higher values for hardness in comparison with SC (P<0.05) and CL (P<0.05). CL showed lower values for hardness and chewiness and higher values for adhesiveness. Dry cured ham obtained from Cinta senese occupied an intermediate position for all characteristics. On the other hand, no significant differences were found when two curing plants, or sex, were compared. The muscle represented a significant source of variability for all rheological characteristics: semitendinosus muscle showed the lowest values for hardness (P<0.001) and chewiness (P<0.05), while Sm muscle had the highest values and BF was characterised by a lower value for adhesiveness and springiness.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)